ANALISIS PERBANDINGAN RENCANA ANGGARAN BIAYA DAN RENCANA ANGGARAN PELAKSANAAN PADA PEMBANGUNAN JALAN DI KOTA PRABUMULIH - Herry Syafrizal; Zuul Fitriana Umari; Bazar Asmawi; Edlin Al Khuzaifah Hasbi (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2026)
Road construction projects undertaken by the Prabumulih City Government involve contractors as service providers. Therefore, project cost evaluation is required to determine whether contractors obtain a profit or incur a loss during implementation. This study aims to determine the Project Implementation Budget (RAP) based on actual material prices, labour wages, equipment costs, and field conditions, and to compare it with the Cost Budget Plan (RAB) for the Nigata Road Construction Project in Sukajadi Subdistrict, Prabumulih City. Primary data were obtained through field measurements, calculation of work volumes, and preparation of the cost estimate for Segment 2. Secondary data consisted of the project RAB, design drawings, the 2023 Unit Price Analysis, and the research location map. The RAB and RAP were calculated using the method applied by the Prabumulih City Public Works and Spatial Planning Agency, particularly in determining coefficients for each work item. The results showed that the RAP for the Nigata Road Construction Project amounted to IDR 862,024,101.46. The comparison between the RAB and RAP indicated a difference of 14.986%. This difference may represent the contractor’s potential profit margin, depending on actual expenditures and conditions encountered during project execution in the field and effective management of available project resources.